Influences of scanning speed on selective laser melting : a computational study - Tang, Chao (2018)
A computational fluid dynamics model based on real physics was developed to investigate the single track formation of selective laser melting. Through simulation works, it is revealed that the wetting behaviour between melted powders and substrate is closely related with the scanning speed of laser beam, thereby affecting the development of interlayer defects and geometry of the solidified track. In addition, a deep and narrow keyhole would be generated with low scanning speed, which contributes to the formation of keyhole voids underneath the solidified track. The simulation results are consistent with experimental observations in literature. Hence the model is helpful to predict the porosity formation of additive manufacturing process even before making real printed parts.